Dump truck object detection dataset including scale-models - Borngrund, Carl (Luleå University of Technology, 2020)
Object detection is a vital part of any autonomous vision system and to obtain a high performing object detector data is needed. The object detection task aims to detect and classify different objects using camera input and getting bounding boxes containing the objects as output. This is usually done by utilizing deep neural networks.

When training an object detector a large amount of data is used, however it is not always practical to collect large amounts of data. This has led to multiple different techniques which decreases the amount of data needed. Examples of such techniques are transfer learning and domain adaptation. Working with construction equipment is a time consuming process and we wanted to examine if it was possible to use scale-model data to train a network and then used that network to detect real objects with no additional training.

This small dataset contains training and validation data of a scale dump truck in different environments while the test set contains images of a full size dump truck of similar model. The aim of the dataset is to train a network to classify wheels, cabs and tipping bodies of a scale-model dump truck and use that to classify the same classes on a full-scale dump truck.

The label structure of the dataset is the YOLO v3 structure, where the classes corresponds to a integer value, such that: Wheel: 0 Cab: 1 Tipping body: 2

Detektering av föremål är en viktig del i de flesta självkörande fordonssystemen och för att nå en hög prestanda behövs data. För att kunna detektera föremål i bilder brukar man använda sig av neurala nätverk. Nätet brukar ta bildinformation som input och resultatet är samma bild där nätet har detekterat, lokaliserat och klassificerat alla föremålen i bilden.

När man tränar ett nät för att utföra denna uppgift brukar stora dataset användas, tyvärr är det inte alltid praktiskt att samla stora mängder data. Detta har lett till att man använder olika tekniker vilket låter oss uppnå bra prestanda med mindre mängd data. Exempel på dessa tekniker är Transfer learning och Domain adaptation. Då det är en väldigt tidskrävande process att arbeta med arbetsfordon ville vi se ifall det var möjligt att använda skalenliga modeller i olika miljöer för att träna ett nätverk och sedan se ifall nätverket kunde detektera liknande föremål på fullskaliga arbetsfordon utan någon extra träning.

Detta mindre datasetet innehåller bilder på en skalenliga dumper i olika miljöer som tränings- och valideringsdata. Testdatat innehåller bilder på en fullskalig dumper av liknande modell. Målet med datasetet är att använda transfer learning eller domain adaptation för att detektera och klassificera tre olika klasser av föremål, hjul, förarhytt och flak.

Beteckningen av datasetet är liknande YOLO beteckningen, där varje klass motsvarar ett heltal. Inom datasetet så är alla klasser skrivna på engelska. Hjul (wheel): 0 Förarhytt (cab): 1 Flak (tipping body): 2
Dump truck object detection dataset including scale-models
Keywords: object detection; objektdetektering; dump truck; tipplastbil; dumper; dumper; Electrical Engineering, Electronic Engineering, Information Engineering; Elektroteknik och elektronik